The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/adfm.201201663
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoshell Nanomicelles for Potential Magnetic Resonance Imaging, Light‐Triggered Drug Release, and Photothermal Therapy

Abstract: A novel multifunctional drug‐delivery platform is developed based on cholesteryl succinyl silane (CSS) nanomicelles loaded with doxorubicin, Fe3O4 magnetic nanoparticles, and gold nanoshells (CDF‐Au‐shell nanomicelles) to combine magnetic resonance (MR) imaging, magnetic‐targeted drug delivery, light‐triggered drug release, and photothermal therapy. The nanomicelles show improved drug‐encapsulation efficiency and loading level, and a good response to magnetic fields, even after the formation of the gold nanosh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
159
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 228 publications
(164 citation statements)
references
References 23 publications
(25 reference statements)
4
159
0
Order By: Relevance
“…Internalized nanoparticles (NPs) to the tumor sites could be stimulated by laser irradiation, to produce localized heat in the range of 40°C-45°C so as to destroy cancer cells. [2][3][4][5] NPs such as single-walled carbon nanotubes, 6 multiwalled carbon nanotubes (MWNTs), 7,8 graphene, 9,10 iron oxide NPs, 11 gold nanorods, 12 and gold nanoshells 13,14 are used to transform NIR radiation to vibrational energy. Therefore, heat generation based on laser irritation could elevate malignant tissues' temperature and destroy tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Internalized nanoparticles (NPs) to the tumor sites could be stimulated by laser irradiation, to produce localized heat in the range of 40°C-45°C so as to destroy cancer cells. [2][3][4][5] NPs such as single-walled carbon nanotubes, 6 multiwalled carbon nanotubes (MWNTs), 7,8 graphene, 9,10 iron oxide NPs, 11 gold nanorods, 12 and gold nanoshells 13,14 are used to transform NIR radiation to vibrational energy. Therefore, heat generation based on laser irritation could elevate malignant tissues' temperature and destroy tumors.…”
Section: Introductionmentioning
confidence: 99%
“…To date, various photothermal agents have been employed to generate heat from light, which results in ablation and succeeding death of cancer cells [23]. Gold nanomaterials such as nanorods [24], nanoshells [25], nanostars [26] and nanocages [27,28] are one of the mostly investigated agents due to their easy accessibility. Yet, recent results indicated that these kinds of photothermal agents suffer from poor photostability under continuous irradiation of NIR light [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Nanomicelles with Au shells are designed to be multifunctional drug-delivery vehicles and to combine bio-imaging, targeting, and light-triggered drug release. 14 Since the first report 1 regarding seed-mediated fabrication of silica-gold nanoshell (SGNS) nearly two decades ago, numerous studies [2][3][4][5][6]8,[13][14][15] have focused on the fabrication of SGNS exhibiting robust structural integrity and the tunable optical resonance by simply adjusting the core-shell ratio across the metal interface, and there have been many attempts to utilize the strong NIR absorption of SGNS as a phototriggered hyperthermia agent on the morbidity of tumor cells. However, there have been concerns regarding the potential human carcinogenicity of silica core materials.…”
Section: Introductionmentioning
confidence: 99%